Enterobius vermicularis appendiceal infestation: a case of false-positive ultrasound-confirmed appendicitis - Cameron J. Elward; Sebrina D. Perkins (Pediatric Emergency Medicine Journal, 2022)
This case report discusses a school-aged boy who presented to the emergency department with diffuse abdominal pain and fever. After investigation, he was found to have Enterobius vermicularis infestation of the appendix without appendicitis. The novelty of this case is the video clip of a live worm-like finding on ultrasound in the boy. The video for this case serves as a reminder for emergency physicians or pediatricians to consider parasitic etiologies in children with abdominal pain, absent some of the classic manifestations like perianal pruritis.